A new species of the genus Mycterodus Spinola (Hemiptera: Auchenorrhyncha: Issidae) from Iran defining southern boundary of generic distribution - Gnezdilov, Vladimir M. (Zootaxa, 2021)
Mycterodus meridionalis sp. n. is described from Kerman Province of southern Iran. This is one of the most southern species of the genus Mycterodus Spinola known from between 29º and 30º of northern latitude.